Akidah Tasawuf (Akhlak, Moral dan Etika): Akhlak, Moral dan Etika - Aji, Ahmad; Junaedi Sitika, Achmad; Farhan Fatah , Ahmad; Tafriji, Ilham (Fakultas Tarbiyah Institut Agama Islam Hamzanwadi Pancor, 2024)
Morals are habits or attitudes that are deep in the human soul where actions arise easily and effortlessly without prior consideration and are carried out repeatedly until they become habits and these actions can lead to good or bad actions. Ethics is a science that studies good and bad by considering human actions rationally, especially in terms of thoughts, feelings and goals of actions, as well as discussing good and bad as well as theories about morals and how to behave in society. Morals are a set of principles, values, or standards that guide human behavior regarding what is considered right or wrong related to ethics and are usually influenced by culture, religion, education, and individual experience. The differences between morals, morals and morals are the part that discusses good and bad issues based on revelation or the Al-Qur'an and hadith.Keywords: morals, morals, ethics